Bimbingan Belajar Bahasa Arab Dasar bagi Anak Usia Dini melalui Kegiatan Karya Wisata - Khoeriyah Ajeng Prasasti; Marsiah Marsiah; Ajahari Ajahari; Surawan Surawan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
Arabic is a foreign language whose position is considered important especially for Muslims. Learning it is sometimes difficult for most people, especially for young children who do not attend madrasa-based schools. This is the reason for the Thematic KKN FTIK IAIN Palangka Raya Students wish to form a small group to teach Arabic to them. In providing learning Arabic, the right strategy is needed so that learning becomes more interactive and not boring. Therefore, by utilizing the Sukamulya Complex side, which incidentally is a tourist area, learning activities are carried out outdoors so that the atmosphere becomes more pleasant. The method used in this activity is the method of games and demonstrations and uses a visual media-based approach in the form of objects around. The result of this activity is that they increase their enthusiasm in learning Arabic, increase their knowledge and insight regarding Arabic vocabulary, and can instill a love of nature through Arabic..